Identification of Metamasius hemipterus (Coleoptera: Dryophthoridae) and its biological control through the use of species of the genus Beauveria and Metarhizium. Amazonas, Peru - Leiva-Espinoza, Santos Triunfo; Román, Alcides; Aguilar, Vilma; Requejo, Elizabeth; Meza-Maicelo, Wagner; Banda-Martinez, Duber; Huaman-Pilco, Ángel Fernando; Loyola, Fredy; Loja, Melissa; Oliva-Cruz, Manuel; Maicelo-Quintana, Jorge (Frontiers in Agronomy, 2026)
Biological control of insect pests represents a key strategy toward sustainable agriculture. This study, focused on the morphological and molecular identification of the sugarcane weevil, Metamasius hemipterus, (Coleoptera: Dryophthoridae), and on the evaluation of the biocontrol potential of four entomopathogenic fungi: Beauveria bassiana, Metarhizium anisopliae, Beauveria peruviensis, and Metarhizium sp. Molecular identification was conducted through phylogenetic analysis, while morphological identification was based on the description of characteristics following established protocols. Both approaches confirmed the identity of the pest as Metamasius hemipterus L. Bioassays were carried out under a completely randomized design, testing four conidial concentrations, plus a control. Metarhizium anisopliae at 1 × 10¹0 conidia/mL was the most virulent, producing the highest mortality and exhibiting the lowest lethal concentration (LC50 = 2.68 × 109 conidia/mL) against Metamasius hemipterus adults. Conversely, Beauveria peruviensis at 1 × 10¹4 conidia/mL achieved the highest colonization efficiency in insect cadavers, with a mycosis rate of 99.4%. These findings indicate that Beauveria peruviensis and Metarhizium anisopliae are promising biological control agents against the sugarcane weevil, the major pest of sugarcane in the Amazonas region of Peru.